Health problems among the aged: a community based study from urban Aligarh, Uttar Pradesh, India - Maroof, Mohd; Ahmad, Anees; Khalique, Najam; Ansari, M. Athar (International Journal Of Community Medicine And Public Health, 2017)
Background: Old age is associated with decline in physical, physiological & cognitive function affecting the quality of life of the elderly population. The robust increase in proportion of elderly has resulted in demographic burden in a developing country like India. To cope up with this burden appropriate & timely intervention is required based on the situational analysis of the health problems faced by the aged population. The objective was to study the prevalence of health problems among elderly population and to find out the relationship of health problems with gender. Methods:This community based observational cross- sectional study was done among 225 individuals aged 60 years & above residing at field practice area of Urban Health Training Centre, JN Medical College, AMU, Aligarh. The data was obtained through pretested & predesigned questionnaire by selecting individuals using systematic random sampling with PPS. Data was entered & analysed by SPSS 20. Test of proportions & Chi square test were applied. P value <0.05 was taken as significant. Results: The present study revealed that the most prevalent problem was cataract (78.2%), followed by depression (35.6%), refractive error (27.6%), locomotor problem (21.3%) and hearing loss (13.8%). The prevalence of hearing loss was significantly related to gender. Conclusions:The study shows that elderly suffers from various physical and mental health problems which shows the need of comprehensive health service to address these problems.